A Chinese herbs complex ameliorates gut microbiota dysbiosis induced by intermittent cold exposure in female rats - Jin, Lu; Bian, Xiangyu; Dong, Weiyun; Yang, Renren; Jing, Che; Li, Xi; Yang, Danfeng; Guo, Changjiang; Gao, Weina (Frontiers in Microbiology, 2022)
Cold is a common source of stress in the alpine areas of northern China. It affects the microbial community, resulting in the invasion of pathogenic microorganisms and intestinal diseases. In recent years, studies have reported that Chinese herbal extracts and their fermentation broth have a significant beneficial effect on gut microbiota. This study aimed to investigate the probiotic effect of a self-designed Chinese herbs complex on the gut microbiota of rats exposed to cold. The rats were treated with intermittent cold exposure and Chinese herbs complex for 14 days, and the gut microbiota composition and other parameters were assayed. The 16s ribosomal DNA high-throughput sequencing and analysis confirmed that the Chinese herbs complex positively improved the gut microbiota. We found that cold exposure could lead to significant changes in the composition of gut microbiota, and affect the intestinal barrier and other physiological functions. The relative abundance of some probiotics in the genus such as Roseburia, Parasutterella, and Elusimicrobium in rats treated with Chinese herbs complex was significantly increased. Serum D-lactic acid (D-LA) and lipopolysaccharide (LPS) were increased in the cold exposure group and decreased in the Chinese herbs complex-treated group. Moreover, the Chinese herbs complex significantly increased the protein expression of occludin. In conclusion, the Chinese herbs complex is effective in restoring the gut microbiota caused by cold exposure, improving the function of the intestinal barrier, and may act as a prebiotic in combatting gut dysbiosis.